Autologous tenocyte injection for the treatment of chronic recalcitrant gluteal tendinopathy: A prospective pilot study - Bucher, T.; Ebert, J.; Smith, Anne; Breidahl, W.; Fallon, M.; Wang, T.; Zheng, M.; Janes, G. (2017)
Background: Gluteal tendinopathy is a common cause of lateral hip pain, and existing conservative treatment modalities demonstrate high symptom recurrence rates. Autologous tenocyte injection (ATI) is a promising cell therapy that may be useful for the treatment of gluteal tendinopathy. Purpose: To investigate the safety and effectiveness of ATI, specifically in patients with chronic recalcitrant gluteal tendinopathy. Study Design: Case series; Level of evidence, 4. Methods: Twelve female patients with a clinical and radiological diagnosis of gluteal tendinopathy were recruited. Patients demonstrated a mean duration of symptoms of 33 months (range, 6-144 months), had undergone a mean 3.2 prior corticosteroid injections (range, 2-5), and had failed to respond to existing conservative treatments including physiotherapy and injections. In an initial procedure, tendon cells were harvested from a needle biopsy of the patella tendon and propagated in a certified Good Manufacturing Practice (GMP) laboratory. In a secondary procedure, a single injection of 2 mL autologous tenocytes (2-5 x 106 cells/mL) suspended in patient serum was injected into the site of the pathological gluteal tendons under ultrasound guidance. Patients were assessed preand postinjection (3, 6, 12, and 24 months) using the Oxford Hip Score (OHS), a visual analog pain scale (VAS), the Short Form-36 (SF-36), and a satisfaction scale. Magnetic resonance imaging (MRI) was undertaken at 8.7 months (range, 6-12 months) postinjection. Results: Molecular characterization of autologous tendon cells showed a profile of growth factor production in all cases, including platelet-derived growth factor a, fibroblast growth factor ß, and transforming growth factor ß. The OHS (mean, 24.0 preinjection to 38.9 at 12 months [14.9-point improvement]; 95% CI, 10.6-19.2; P <.001), VAS (mean, 7.2 preinjection to 3.1 at 12 months [4.1-point improvement]; 95% CI, 2.6-5.6; P <.001), and SF-36 (mean, 28.1 preinjection to 43.3 at 12 months [15.2-point improvement]; 95% CI, 9.8-20.5; P <.001) significantly improved to 12 months postinjection, sustained to 24 months. Eight patients were satisfied with their outcomes. Significant MRI-based improvement could not be demonstrated in the majority of cases. Conclusion: ATI for gluteal tendinopathy is safe, with improved and sustained clinical outcomes to 24 months.